Comparison of Mean Duration of Postoperative Analgesia Following QL2 Block Versus QL3 Block Using Ropivacaine 0.25% In Patients Undergoing Unilateral Inguinal Hernia Repair - Muhammad Ayaz; Ambreen Khan; Anam Mahmood; Muhammad Usman; Qazi Anees Ahmad; . Iqra; Qandeel Kokab; Muhammad Hammad (Pakistan Journal of Health Sciences, 2026)
Effective postoperative pain management after inguinal hernia repair enhances recovery and reduces opioid use. Among quadratus lumborum block variants, evidence remains uncertain as to whether the posterior (QLB-2) or trans-muscular (QLB-3) approach provides superior analgesia. Objectives: To compare the mean duration of postoperative analgesia produced by posterior quadratus lumborum block (QLB-2) and trans-muscular quadratus lumborum block (QLB-3) using 0.25% ropivacaine in patients undergoing unilateral inguinal hernia repair. Methods: The randomised controlled trial was conducted in the Department of Anaesthesia at Bahawal Victoria Hospital, Bahawalpur, from July to December 2024. Sixty-four male patients aged 18-50 years who underwent unilateral inguinal hernia repair under general anaesthesia were included and randomly divided into two groups of 32 participants each. Group QLB-2was given the posterior quadratus lumborum block, and Group QLB-3 was given the trans-muscular approach. Twenty millilitres of 0.25% ropivacaine was applied in both groups under ultrasound guidance. The visual analogue scale (VAS) was used to measure postoperative pain, and the duration of analgesia was defined as the time from entering the recovery room to achieving a VAS score>3. Results: The mean time to first analgesic request was significantly longer in QLB-3 (457.7 ± 161.3 min) than in QLB-2 (271.8 ± 94.6 min; p